Sars-Co-2 Vaccine Adverse Effects (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Vaccine adverse effects VAE is one of the most vital areas of human mass vaccination programs.Covid-19 vaccines are not an exception to this theme. Covid -19 VAE occupied the forefront area in the current covid-19 vaccine research. It broadly categorized into simple and complex or serious VAE. The simple account for tender and swelling in muscle injection sites ,as well as fever. The complex or serious VAE can be ramified into vaccine associated enhancement of disease VAE and Vaccine failure VF. Both of VAE and VF are a matter of debate in covid-19 vaccine manufacturing holds. Though they were currently reportable all over the world.Methods : The present work aimed at a ; follow up report of VAED and VF cases in the post-vaccination period .Results: Immune vascular embolism in lungs and in the lower left arterial embolism in leg , thermbo-cytopenia ,cardio-pathy, atopic and delayed skin hypersensitivity. While VF was as break through sars-cov-2 infection as pulmonary , gastric and long forms. A total of 20 cases which account for0.026 per thousand of the total vaccine coverage during the study period in this area..Conclusion: The immune mechanisms behind each of VAE cases were discussed. These findings stands as a novel contribution in this area.